2016
DOI: 10.1109/lcomm.2016.2584603
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Hypothesis Testing for Cooperative Sequential Spectrum Sensing Under Noise Uncertainty

Abstract: Efficient and reliable spectrum sensing is extremely significant, especially in the presence of noise uncertainty in low SNR environment below which conventional detectors fail to be robust. In this letter, by development of a sequential probability ratio test (SPRT) for the fuzzy hypothesis testing (FHT), we propose a novel cooperative sequential detector to deal with the effect of noise power uncertainty. In this approach, for every measurement, FHT is computed by each cognitive radio. Subsequently, fusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Alternatively different from the above approaches researchers have tried to solve this limitation of energy detector by adopting soft decision method using Fuzzy logic [18,27,19,20,9] as there is great deal of ambiguity, uncertainty or fuzziness in the 'confused region' as shown in Figure 1 for a cooperative sensing scenario. The disadvantages cooperative based sensing are the increased hardware overhead as well as sensing latency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively different from the above approaches researchers have tried to solve this limitation of energy detector by adopting soft decision method using Fuzzy logic [18,27,19,20,9] as there is great deal of ambiguity, uncertainty or fuzziness in the 'confused region' as shown in Figure 1 for a cooperative sensing scenario. The disadvantages cooperative based sensing are the increased hardware overhead as well as sensing latency.…”
Section: Related Workmentioning
confidence: 99%
“…is the Q-function, γ is the received SNR of the signal, P D is probability of detection, P FA is the probability of false alarm, P MD is the probability of miss detection. The threshold computation as per Neymen-Pearson criterion [20] is,…”
Section: Conventional Energy Detectormentioning
confidence: 99%
“…The existing policy of spectrum allocation works on static mode, where the available frequency spectra are divided into subbands. Each subband is exclusively assigned to the specific service provider, known as licensed user or primary user (PU) . However, based on the recent published reports of Federal Communications Commission in USA and few other regulatory bodies, eg, Office of Communications in UK, it is found that major portions of the allocated RF spectra are underutilized by the licensed users .…”
Section: Introductionmentioning
confidence: 99%
“…Each subband is exclusively assigned to the specific service provider, known as licensed user or primary user (PU) . However, based on the recent published reports of Federal Communications Commission in USA and few other regulatory bodies, eg, Office of Communications in UK, it is found that major portions of the allocated RF spectra are underutilized by the licensed users . Cognitive radio (CR) communication mitigates this spectrum underutilization problem by allowing the CR/secondary users (SUs) either to access the spectrum opportunistically (when PU is not transmitting) or share the same frequency band with PU subject to meeting its tolerable interference .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation